(untitled) (Transport systems and technologies, 2020)
The article presents a mathematical model of joint oscillations of the car-platform for piggyback transportations and semi-trailer truck. Considered forced oscillations of the investigated object in the vertical plane of symmetry. Built a design scheme of the platform with mounted on it with a tractor and trailer system are presented in the form of a mechanical system, all bodies which, in addition platform, accept hard. The supporting structure of the platform is presented in the form of elastic massless beams carries seven lumped masses. A railway track is considered inertial with elastic-dissipative properties. In the simulation work for suspension updated power characteristic of the friction damper. As disturbances acting on the wheelset of the platform, considered butt roughness of the track. According to the results of computer simulation obtained measurements of vertical dynamics, piggyback platforms depending on the stiffness and characteristics of the oscillations damping. The obtained data dynamic calculations allowed us to estimate the schemes of fastening of a semi-trailer truck and to determine the influence on the dynamic indexes of changes in the stiffness of the spring suspension and the coefficient of friction relative to wedge the damper through adjustment of a spring set. Proved the feasibility of the decision on the free installation of the train on the platform, allowing automotive suspension gets the opportunity to actively damping the perturbations transmitted to the wheels of the road train from the platform.